Extracellular enzyne screening of fungal endophytes from Pandan, Antique and Nueva Valencia, Guimaras, Philippines. - Tumulak, Danica Marie G. (2019.)
Fungal endophytes had been examined for the past several years in search for new bioactive compounds. Among these are the fungal enzymes which are generally more stable than enzymes of other sources and are used in processing of raw materials in beverages, food, textile, and other major industries. In the host plant, endophytic enzymes are degraders of available polymers such as starch and cellulosr. Fast screening of these enzymes from a large number of fungi can be done with the use of solid media. Twenty-five endophytic fungi isolated from two beach forest species Pandanus tectorius and Planchonella obovata, two seagrass species Cymodocea rotundata and Halophilia ovalis, and two seaweed species Halimeda sp. and Sargassum sp. from Pandan, Antique and Nueva Valencia, Guimaras, Philippines were screened for extracellular enzymes which are amylase, cellulose, laccase, lipase, and protease. Ninety-two percent of fungi screened were positive for lipase, 88% for amylase and protease, 84% for cellulose, and 24% for laccase. The fungi tested differ in the type and amounts of enzymes they produced based on the enzyme index. These fungi represent potential sources of enzymes for various applications. However, there is still a need to study their role in their host plants.
Special Problem (Undergraduate, Bachelor of Science in Biology.
Keywords: Fungal Endophytes -- Pandan, Antique; Fungal Endophytes -- Nueva Valencia, Guimaras